An online survey of personal mosquito-repellent strategies - Moore, Emily Lucille; Scott, Mary Alice; Rodriguez, Stacy Deadra; Mitra, Soumi; Vulcan, Julia; Cordova, Joel Javierla; Chung, Hae-Na; de Souza, Debora Linhares Lino; Gonzales, Kristina Kay; Hansen, Immo Alex (PeerJ, 2018)
Background Mosquito repellents can be an effective method for personal protection against mosquito bites that are a nuisance and carry the risk of transmission of mosquito-borne pathogens like plasmodia, dengue virus, chikungunya virus, and Zika virus. A multitude of commercially available products are currently on the market, some of them highly effective while others have low or no efficacy. Many home remedies of unknown efficacy are also widely used. Methods We conducted a survey study to determine what kind of mosquito repellents and other mosquito control strategies people use. Our online survey was focused on unconventional methods and was answered by 5,209 participants. Results The majority of participants resided in the United States, were female (67%), had higher education (81% had a university degree), and were 18 to 37 years old (50%). The most commonly used repellent was DEET spray (48%), followed closely by citronella candles (43%) and ‘natural’ repellent sprays (36%). We collected a plethora of home remedies and other strategies people use that warrant further research into their effectiveness. Discussion Our study lays the foundation for future research in alternative, unconventional methods to repel mosquitoes that may be culturally acceptable and accessible for people.
Keywords: Survey; Mosquito; Repellents